Meat-eating & human evolution - Stanford, Craig B. (Craig Britton), 1956-; Bunn, Henry Thomas (Human evolution series., 2001)
Preface. Forword. Introduction. I MEAT-EATING AND THE FOSSIL RECORD. 1. Deconstructing the Serengeti. 2. Taphonomy of the Swartkrans hominid postcrania and its bearing on issues of meat-eating and fire management. 3. Neanderthal hunting and meat-processing in the Near East: evidence from Kebara Cave (Israel). 4. Modeling the edible landscape. II LIVING NONHUMAN ANALOGS FOR MEAT-EATING. 5. The dog-eat-dog world of carnivores: a review of past and present carnivore community dynamics. 6. Meat and the early human diet: insights from Neotropical primate studies. 7. The other faunivory: primate ins.